Ferrokinetics is associated with the left ventricular mass index in patients with chronic kidney disease. Issue 4 (4th July 2017) - Tanaka, Akihito; Inaguma, Daijo; Watanabe, Yu; Ito, Eri; Kamegai, Naoki; Shimogushi, Hiroya; Shinjo, Hibiki; Koike, Kiyomi; Otsuka, Yasuhiro; Takeda, Asami
Abstract: Background Patients with chronic kidney disease (CKD) often have the complication of anaemia. Usage of an erythropoietin-stimulating agent accelerates iron deficiency because it promotes iron utilization. Recently, iron administration was reported to be effective for patients with cardiac failure. We examined the association between ferrokinetics and cardiac function in patients with CKD. Methods In this cross-sectional study, we examined 558 patients (424 men and 134 women; mean age, 68.9 ± 13.1 years) with CKD who were admitted to our hospital. We assessed cardiac function by ultrasonography and ferrokinetics through transferrin saturation (TSAT) and ferritin levels. Results The primary diseases of CKD were nephrosclerosis (n = 247), diabetic nephropathy (n = 154), chronic glomerulonephritis (n = 73), and others. The mean estimated glomerular filtration rate was 16.9 ± 9.3 mL/min/1.7 m 2, and the haemoglobin (Hb) level was 11.0 ± 1.7 g/dL. The median of TSAT was 28.05%, and patients were divided into two groups: below (L-Ts) and above (H-Ts) the median. The median of ferritin was 122 ng/mL, and patients were divided into two groups: below (L-f) and above (H-f) the median. We categorized four groups as H-Ts + H-F, H-Ts + L-F, L-Ts + H-F, and L-Ts + L-F. The Hb levels were 11.1 ± 1.8, 11.3 ± 1.4, 10.9 ± 1.6, and 10.8 ± 1.5 g/dL, respectively, and there was no difference between groups. However, the left ventricular mass indices (LVMIs) were 122.6 ± 46.6, 110.8 ± 32.0, 118.3 ± 36.0, 126.7 ± 46.9, respectively ( P = 0.0291). This tendency was stronger in patients without cardiovascular events. Conclusion In patients with CKD, there is an association between ferrokinetics and LVMI. We have to be mindful not only of anaemia but also of ferrokinetics.